Emergent symmetries at criticality in multi field RFT/DP - Jochen Bartels; Carlos Contreras; Gian Paolo Vacca (Journal of High Energy Physics, 2024)
Abstract We study multifield extensions of Reggeon Field Theory (also equivalent to Directed Percolation model) at criticality in the perturbative ϵ-expansion below the upper critical dimension D c = 4 at one loop, for the special case when all fields have the same scale (anomalous) dimensions. Analyzing all the fixed points of the renormalization group flow for N = 2 flavors and some for N = 3, we find scale invariant solutions which are characterized by specific emergent global symmetries of the interacting potential. We also study two infinite families as a function of N having ℤ N and S N+1 symmetries.